Analisis Kegawatdaruratan pada Sport Event berdasarkan Perspektif Persiapan Kondisi Darurat (Emergency Preparedness) - Anisa Wardhani; Muhammad Iqbal Katik Rajoendah; Firman Syah; Christina L. Rudatin (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2023)
The match between Arema vs Persebaya in Kanjuruhan, Malang, Indonesia experienced riots which resulted in hundreds of spectators being injured and dead. This incident became the world's attention, not only because of the large number of victims but also because of the alleged mistakes in the preparation for the match which did not prioritize the emergency aspect. This article will analyze these events from the perspective of emergency preparedness in the context of risk management. Preparation for emergency conditions in the context of risk management is very closely related to preparedness, namely a series of activities carried out to anticipate disasters through organizing and through effective and efficient steps. (Mardiatno, 2019). This study will analyze the things that need to be considered in organizing competitions with large crowds such as in Kanjuruhan from the perspective of Emergency Preparedness. The method used in this study is a qualitative method using content analysis. The results of the analysis show that several aspects of emergency preparedness must receive in-depth attention as the cause of the high level of risk occurring in the match.